The Relationship Between Serum Folate Level and Residual Renal Function in CAPD Patients - Yu J; Zhou Q; Xu Y; Wang T; Du J; Zhao L; Li J; Wang H; Xu Q; Lai X; Guo Z (International Journal of General Medicine, 2022)
Jianpeng Yu,1,* Qi Zhou,1,* Ying Xu,1,* Tieyun Wang,1 Jun Du,1 Lifang Zhao,1 Juan Li,1 Haiyan Wang,1 Qianqian Xu,2 Xueli Lai,1 Zhiyong Guo1 1Department of Nephrology, Shanghai Changhai Hospital, Shanghai, People’s Republic of China; 2Department of Rheumatology and Immunology, Shanghai Changhai Hospital, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xueli Lai; Zhiyong Guo, Email laixueli_changhai@163.com; drguozhiyong@163.comObjective: To investigate the relationship between serum folate (FA) levels and residual renal function (RRF) in continuous ambulatory peritoneal dialysis (CAPD) patients.Methods: Clinical data were collected from 180 hospitalized patients who received CAPD regularly. Patients were divided into the FA deficiency group and the FA non-deficiency group according to serum FA level. Data on age, sex, PD vintage, hemoglobin, mean corpuscular volume, serum FA, total Kt/V, residual kidney Kt/V, peritoneum Kt/V, creatinine clearance (Ccr), ultrafiltration volume, cystatin C (cytC), serum creatinine (Scr), urea nitrogen, retinol-binding protein and the primary disease were gathered from 2 groups. Statistical methods were used to analyze the relationship between serum FA level and RRF.Results: Peritoneal Kt/V, cytC, Scr were higher, and residual kidney Kt/V was lower in FA deficiency group than in non-deficiency group. Univariate correlation showed the peritoneal Kt/V, cytC, Scr negatively correlated with serum FA while residual kidney Kt/V positively correlated with serum FA, and there was a simple linear regression relationship between serum FA and residual kidney Kt/V. Differences were statistically significant (P< 0.05).Conclusion: There is a relationship between serum FA and RRF in CAPD patients. Prospective studies or trials should be performed to clarify the importance of FA supplementation on RRF during peritoneal dialysis.Keywords: folate, continuous ambulatory peritoneal dialysis, residual renal function